The Effect of Intake Air Temperature on Engine Performance and Fuel Consumption of Passenger Car - Bin Khaifullizan, Muhammad Nazmi Naufal; Mohmad Ja’at @ Mohd Noh, Md Norrizam; Zainal Abidin, Shaiful Fadzil (Progress in Engineering Application and Technology, 2021)
An internal combustion engine (ICE) is a combustion process that occur inside the combustion chamber of the engine. There are 3 elements required for the internal combustion engine (ICE) which are air, fuel and ignition. These 3 elements determined the performance of a vehicle based on torque and power produced by the engine. In this research, it presents the study of the effect of air intake temperature on engine performance and fuel consumption of a passenger car. This research has been conducted with laboratory setup to analyse the fuel consumption and engine performance of the test vehicle when the air intake temperature increases. The temperature of air intake has been controlled by using heating system. The engine performance and fuel consumption have been measured using Mustang Chassis Dynamometer and On-Board Diagnostic 2 (OBD II). The test is conducted using Perodua Myvi 1.3L with different air intake temperature which are 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C and 70°C. The fuel consumption and engine performance produced by the engine of the test vehicle was studied. Generally, fuel consumption decreases when the air intake temperature increases at both idle and running condition. This is because the oxygen availability inside the hot air is lower than cold air. Thus, it required small amount of fuel for combustion. This resulted in lower amount of torque and power produced by the engine when the temperature of air intake increases. The overall result shows that the engine performance is better at low air intake temperature compared high air intake temperature. The result of the experiment that was conducted become a useful source of references for those who wish to continue study on the related subject.